2018
DOI: 10.3390/toxins10110472
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Mycotoxin Characterization of Alternaria Species Isolated from Wheat Grown in Tuscany, Italy

Abstract: Wheat, the main source of carbohydrates worldwide, can be attacked by a wide number of phytopathogenic fungi, included Alternaria species. Alternaria species commonly occur on wheat worldwide and produce several mycotoxins such as tenuazonic acid (TA), alternariol (AOH), alternariol-monomethyl ether (AME), and altenuene (ALT), provided of haemato-toxic, genotoxic, and mutagenic activities. The contamination by Alternaria species of wheat kernels, collected in Tuscany, Italy, from 2013 to 2016, was evaluated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 41 publications
6
37
1
7
Order By: Relevance
“…Our results indicate that population structure of Alternaria species associated with black point disease, is prevalently represented by A. tenuissima and A. alternata (about 50% of total strains tested), as observed in previous studies [7,9]. Moreover, A. arborescens was also identified in wheat in accordance with other recent studies in Argentina [18,47], Tunisia [48], Germany, and Russia [49].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our results indicate that population structure of Alternaria species associated with black point disease, is prevalently represented by A. tenuissima and A. alternata (about 50% of total strains tested), as observed in previous studies [7,9]. Moreover, A. arborescens was also identified in wheat in accordance with other recent studies in Argentina [18,47], Tunisia [48], Germany, and Russia [49].…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, molecular studies revealed multiple non-monophyletic species within Alternaria complex and Alternaria species clades which do not always correlate to a species-group based upon morphological characteristics [7,14,[40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations